A Study of Mechanical Properties of Polymethl Methacrylate Polymer Reinforced by Silica Particles (Sio2) - Jawad Kadhim Oleiwi; Farhad Mohammad O.Kushnaw; Israa Faisal qhaze (Engineering and Technology Journal, 2013)
In this research the mechanical properties of PMMA polymer reinforced by ceramic particles (silica) has been investigated. Many tests are performed on these composites. The effects of the particles size and volume fraction on the mechanical properties which include: ultimate tensile strength, elongation percentage, modulus of elasticity, bending modulus, flexural strength, max. shear stress, impact strength and fracture toughness were studied. Statistical and mathematical analyses were used to the processing of the experimental data. Mathematical models were done which show the mechanical properties of composite materials as a function of particles size and volume fraction. The results had revealed that the values of modulus of elasticity, elongation percentage, tensile strength, bending modulus and max. shear stress increase with the addition of SiO2 particles and with the increase of the volume fraction of them and its reach the maximum value at (12% vol.) and (25 mm) particles size. The values of fracture toughness and impact energy decrease with increase of volume fraction. Silica particles with small particles size improved these properties more than that of large particles size.